New luminescent mycenoid fungi (Basidiomycota, Agaricales) from São Paulo State, Brazil. (1st November 2016) - Desjardin, Dennis E.; Perry, Brian A.; Stevani, Cassius V.
Abstract: Four species of mycenoid fungi are reported as luminescent (or putatively luminescent) on the basis of specimens collected from São Paulo State, Brazil. Two of them represent new species ( Mycena oculisnymphae, Resinomycena petarensis ), and two represent new reports of luminescence in previously described species ( M. deformis, M. globulispora ). Comprehensive descriptions, illustrations, photographs, and comparisons with phenetically similar species are provided. Sequences of nuc rDNA internal transcribed spacer regions were generated for barcoding purposes and for comparisons with similar species.